2013
DOI: 10.1155/2013/351680
|View full text |Cite
|
Sign up to set email alerts
|

Preserved Transcallosal Inhibition to Transcranial Magnetic Stimulation in Nondemented Elderly Patients with Leukoaraiosis

Abstract: Structural corpus callosum (CC) changes in patients with leukoaraiosis (LA) are significantly associated with cognitive and motor impairment. The aim of this study is to investigate the transcallosal fibers functioning by means of transcranial magnetic stimulation (TMS) in elderly patients with LA. The resting motor threshold (rMT), the motor-evoked potentials (MEPs), and the controlateral (cSP) and ipsilateral silent periods (iSP) were determined using single-pulse TMS in 15 patients and 15 age-matched contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 38 publications
(37 reference statements)
0
36
0
Order By: Relevance
“…These symptoms may even present in the preclinical or early stages of these diseases (Bella et al., 2011a, 2011b, 2013; Lanza et al., 2013; Pennisi et al., 2016; Lanza et al., 2017). …”
Section: Introductionmentioning
confidence: 99%
“…These symptoms may even present in the preclinical or early stages of these diseases (Bella et al., 2011a, 2011b, 2013; Lanza et al., 2013; Pennisi et al., 2016; Lanza et al., 2017). …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a total of 46 papers were eventually included in this study ( Figure 1) and the main findings are summarized in Table 1. More in details, 8 studies deal with serum biomarkers [9][10][11][12][13][14][15][16], 10 with cerebrospinal fluid (CSF) [17][18][19][20][21][22][23][24][25][26], 4 with neuroimaging [27][28][29][30], 6 with histopathology [31][32][33][34][35][36], and 14 with transcranial magnetic stimulation (TMS) [37][38][39][40][41][42][43][44][45][46][47][48][49][50]; 4 studies included more than one technique: one studied both serum and CSF markers [51], two both serum and neuroimaging [52,53], and one both CSF and neuroimaging…”
Section: Resultsmentioning
confidence: 99%
“…A two-year follow-up study in the same patients showed an increase of the global cortical excitability (reduction of the median rMT), along with a significant cognitive worsening [41], thus suggesting the role of the enhanced ICF at baseline as a predictor of cognitive and TMS progression. Finally, unlike MCI and AD, TMS measures of transcallosal functioning appeared to be spared in mild VCI, suggesting a role of the interhemispheric integrity in holding cognitive performance up in these patients [42].…”
Section: Transcranial Magnetic Stimulationmentioning
confidence: 88%
See 1 more Smart Citation
“…a) Post-ischemic encephalopathy with several types of predominant distribution pattern: (1) Recent neurophysiological studies using transcranial motor stimulation (TMS) have revealed distinct patterns of cortical excitability in VaD, possibly associated with disease process and progress [43,44]. However, the pathophysiological details of VCI/VaD and of vascular depression (VaDep -see consensus paper [45]) are beyond the scope of this mini-review.…”
Section: Other Pathological Substrates Of Vci Includementioning
confidence: 99%